Peningkatan Kapasitas SDM Guru Melalui Pelatihan Penggunaan Bamboozle Dan Quizziz Dalam Pembelajaran Interaktif di SMA Negeri 3 Palangka Raya - Sanjayanto Nugroho; Aprilita Aprilita; Nurlia Eka Damayanti; Novera Kristianti (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
This article discusses increasing the capacity of teachers' human resources (HR) through training in using the Bamboozle and Quizziz digital platforms in interactive learning. The main problem faced is the lack of teacher skills in using educational technology, which has an impact on the level of student participation in the learning process which is still low. The aim of this research is to improve teachers' skills in utilizing digital platforms to create more dynamic and participatory learning. The method used is intensive training involving theory sessions and direct practice for teachers at SMA Negeri 3 Palangka Raya. The results of the training showed a significant increase in teacher skills, which had a positive impact on student engagement during the teaching and learning process. The conclusion of this article is that integrating technology such as Bamboozle and Quizziz can be an effective solution to face the challenges of the digital era, including creating an interactive and more interesting learning environment.